1983
DOI: 10.1136/bjsm.17.2.84
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthrosis in runners with knee pain.

Abstract: A clinical and radiological study of the knee joints of twenty middle and long distance runners, complaining of knee pain, was carried out. Osteoarthrosis of varying degree was found in six of the runners. A torn meniscus requiring surgery was found in one athlete, and another had considerable ligamentous laxity -both of these conditions predispose to the development of degenerative changes. Degenerative changes were significantly associated with the presence of genu varum (p < 0.01) and history of severe inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…Four of these six patients had a history of a major knee injury, which, presumably, had increased the vulnerability of their joint. 20 Of the 14 patients without radiographic OA, only 3 had had a major knee injury previously.…”
Section: Loading Factorsmentioning
confidence: 98%
“…Four of these six patients had a history of a major knee injury, which, presumably, had increased the vulnerability of their joint. 20 Of the 14 patients without radiographic OA, only 3 had had a major knee injury previously.…”
Section: Loading Factorsmentioning
confidence: 98%
“…However, Marti et al (1989) found radio- logically more degenerative changes in the hip joints of former national team long-distance runners than in bobsleigh competitors and the reference population [53]. Also, runners who had sustained injuries, or who had anatomical abnormalities but continued running training, showed accelerated development of OA in affected joints [54]. Different types of exercise or sports activities, which repetitively expose joints to high levels of impact or torsional loading, are associated with increased prevalence of OA [55][56][57][58][59][60].…”
Section: Increased Joint Loading and Weight-bearingmentioning
confidence: 99%
“…30,63,98,102 A study of 20 middle-aged runners with knee pain for at least 3 months suggested that joint abnormalities may be related to the development of degenerative disease in association with running. 73 In this investigation, 20 individuals with a mean age of 39 years who had run an average of 62 miles a week for 20 years were examined clinically and radiographically. Six of the 20 had evidence of degenerative joint disease.…”
Section: Factors That Increase the Risk Of Joint Injury And Degenerationmentioning
confidence: 99%
“…102 This latter observation supports the concept that age increases the vulnerability of articular cartilage to the development of degenerative changes, possibly because of loss of the ability of chondrocytes to maintain and restore the articular surface. [66][67][68][69][70][71][72][73][74][75][76][77] The age-related decline in chondrocyte function, a phenomena referred to as cell senescence, 66,68,70 may be accelerated by joint injuries and residual joint instability following injury.…”
Section: Factors That Increase the Risk Of Joint Injury And Degenerationmentioning
confidence: 99%